Analisis Implementasi Balanced Scorecard Berbasis ESG (Environmental, Social, Governance) dalam Meningkatkan Nilai Perusahaan - Nabila, Nabila; Purwanti, Purwanti (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the implementation of the ESG (Environmental, Social, Governance)-based Balanced Scorecard to enhance corporate value. The Balanced Scorecard is utilized as a managerial tool to integrate ESG aspects into corporate strategy and performance measurement. This research adopts a quantitative approach using multiple regression analysis to examine the relationship between ESG indicators, Balanced Scorecard perspectives, and corporate value. The findings reveal that ESG integration within the Balanced Scorecard positively contributes to corporate value improvement through enhanced financial performance, operational efficiency, and reputation. The study's implications provide insights for companies to adopt measurable sustainability strategies to support sustainable growth and create long-term value for stakeholders.